Dermatitis Kontak Iritan Kronik Pada Pekerja Penyadap Karet: Laporan Kasus - Ni Komang Devi Wiratningrum; Winda Trijayanthi Utama (Medula, 2026)
Irritant contact dermatitis (ICD) is one of the most common occupational skin diseases and is caused by direct and repeated exposure to irritant substances. Workers in the rubber plantation sector are at high risk of developing ICD due to exposure to natural rubber latex and chemicals such as ammonia solution used in the latex processing process. This case report aims to describe a case of chronic irritant contact dermatitis in a rubber tapper. A 50-year-old male presented with a burning sensation on both palms for the past three months, accompanied by erythema, pruritus, dry skin, and scaling. The patient had been working as a rubber tapper for 10 years and was frequently exposed to latex and ammonia solution without using personal protective equipment. Dermatological examination revealed erythematous plaques with diffuse hyperpigmentation and ill-defined borders on the bilateral palmar and plantar regions, accompanied by xerosis, coarse scales, fissures, lichenification, and hyperkeratosis. Based on the history, occupational exposure to irritants, and clinical findings, the patient was diagnosed with chronic irritant contact dermatitis. Management included topical therapy and patient education to avoid irritant exposure and to use personal protective equipment while working. This case highlights the importance of identifying occupational risk factors in establishing the diagnosis and emphasizes preventive measures to reduce irritant exposure in order to prevent disease recurrence.